Bound feet, young hands : tracking the demise of footbinding in village China - Bossen, Laurel, 1945-; Gates, Hill (Stanford University Press, 2017)
Footbinding was common in China until the early 20th century, when most Chinese were family farmers. Why did these families bind young girls' feet? And why did footbinding stop? Here, Laurel Bossen and Hill Gates upend the popular view of footbinding as a status, or even sexual, symbol by showing that it was an undeniably effective way to get even very young girls to sit still and work with their hands.